Hateship, Friendship, courshif, Loveship, marriage / Alice Munro ; penerjemah, Rahmani Astuti ; penyunting, Ika Yuliana Kurniasih - MUNRO, Alice; Rahmani Astuti; Ika Yuliana Kurniasih (Bintang, 2016)
446 hlm ; 21cm